How - and How Much? An Analysis of Major Conflict Lines Regarding the Transformation of German Animal Farming - Philipp von Gall; Jor̈g Luy; Moritz Kod̈er; Marie von Meyer-Hof̈er (German Journal of Agricultural Economics (GJAE), 2024)
Based on the concept of a 'future workshop', this paper contributes to the understanding of major conflict lines and future pathways for animal farming in Germany. Participants in the future workshop were tasked with outlining their ideal vision of the future of animal farming, focusing on both its mode and quantity. We found three different types of visions differing in their motivation, farming methods, and the scale of envisioned animal farming: 'Higher Standards' (V1), 'System Change and Reduction' (V2), 'Alternatives to Animal Farming' (V3). V1 seeks to secure the quantities of supply and demand of animal products in Germany with minor adjustments towards improved animal welfare and investments in resource-efficiency and climate friendliness. V2 advocates for comprehensive social and environmental systemic changes throughout the agri-food sector, with substantially fewer animals involved. V3 aims to replace animal farming, with plant-based and other alternatives, whenever and wherever possible. Our findings suggest that there is little ground for a societal consensus on a single future mode and scale of animal farming. Stakeholder dialogues and policy initiatives should therefore allow for different pathways while focusing on compromises in the near future. Short-term solutions may be acceptable to supporters of all three visions, however, achieving this requires reframing the debate from 'securing the future of animal farming' to 'guiding the future of animal farming', acknowledging the potential - albeit partly - replacement of animal farming by suitable alternatives.
Keywords: 330; Future of Animal Farming; Future of Food; Sustainable Transformation; Social Acceptance of Agricultural Policies; Stakeholder Dialogue